The Rise of Domestic Capital Markets for Corporate Financing - Abraham, Facundo; Cortina, Juan J.; Schmukler, Sergio L. (World Bank, Washington, DC, 2019)
During the past decades, firms from emerging economies have significantly increased the amount of financing obtained in capital markets. Whereas the literature argues that international markets have been an important contributor to this process, the role of domestic markets is mostly unknown. By examining the case of East Asia, this paper shows that domestic markets have been a key driver of the observed trends in capital market financing since the early 2000s. As domestic markets developed, more and smaller firms gained access to equity and corporate bond financing. Domestic markets also helped some corporations to diversify funding sources and obtain domestic currency financing. Policy reforms following the Asian Financial Crisis accompanied the growth of domestic markets. Part of the reforms were aimed at developing domestic capital markets for small and medium-size enterprises. Although these markets have developed significantly, they still serve relatively few corporations, albeit from new sectors.